Serum lipoprotein (a) predicts acute coronary syndromes in patients with severe carotid stenosis. (2nd February 2018) - Rigamonti, Fabio; Carbone, Federico; Montecucco, Fabrizio; Bonaventura, Aldo; Liberale, Luca; Burger, Fabienne; Roth, Aline; Bertolotto, Maria; Spinella, Giovanni; Pane, Bianca; Palombo, Domenico; Pende, Aldo; et al.
Abstract: Background: Different cut‐off values of serum lipoprotein (a) [Lp (a)] were recently identified to better stratify cardiovascular risk categories. Both pathophysiological and prognostic values of Lp (a) remain unclear. Materials and methods: Here, the prognostic value of Lp (a) and its correlation with intraplaque features were assessed in patients with severe carotid artery stenosis undergoing endarterectomy (n = 180). The cut‐off value of 10 mg/dL for serum Lp (a) was selected to predict 24‐month follow‐up acute coronary syndrome (ACS). In addition, the association between serum Lp (a) and intraplaque lipids, collagen, inflammatory and vascular cells was assessed. Serum Lp (a) levels were measured by nephelometric assay. Results: Patients with high Lp (a) had similar comorbidities, medications and laboratory parameters as compared to low Lp (a) levels. At 24‐month follow‐up, patients with high Lp (a) had more ACS as compared to low levels. Histological parameters within plaques were comparable in the study groups. No significant correlation between Lp (a) serum levels and intraplaque parameters was found, except for a weak positive association with smooth muscle cells in upstream plaque portions. When adjusted for gender, the presence of dyslipidaemia and chronic coronary artery disease, Lp (a) ≥10 mg/dL remained predictive for ACS. Conclusions: Lp (a) determination could be a useful tool to predict ACS in patients with severe carotid stenosis.